1998
DOI: 10.1159/000045020
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Excretion of Tamm-Horsfall Protein and Epidermal Growth Factor in Chronic Nephropathy

Abstract: Tamm-Horsfall protein (THP) and epidermal growth factor (EGF) are both synthesized by tubular cells in the distal part of the nephron and excreted with the urine. The present study examines the urinary excretion rates of the two peptides in relation to functional tubular markers in patients with chronic nephropathy. Four groups of patients with moderate to severely reduced renal function were studied: glomerulonephritis (n = 10), diabetic nephropathy (n = 11), tubulointerstitial nephropathy (n = 13), and polyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
7
24
0
Order By: Relevance
“…Nevertheless, because reduced urinary excretion of uromodulin has been reported in several nephropathies, it is not clear whether the reduction observed in patients with MCKD2/FJHN may be secondary to distal tubule damage. 74, 75 …”
Section: Fine Mechanisms Related To Delayed Cell Maturation and Storagementioning
confidence: 99%
“…Nevertheless, because reduced urinary excretion of uromodulin has been reported in several nephropathies, it is not clear whether the reduction observed in patients with MCKD2/FJHN may be secondary to distal tubule damage. 74, 75 …”
Section: Fine Mechanisms Related To Delayed Cell Maturation and Storagementioning
confidence: 99%
“…2B). In the more distal regions resided three stretches of CA (46) repeat and an Alu-Sx repetitive sequence. A computer-assisted sequence search of the 5Ј-flanking region of the mouse THP gene against the Web-based TRANSFEC database and FindPatterns of SeqWeb 1.2 revealed a number of consensusrecognition sequences for known transcription factors.…”
Section: Thp Is Kidney Specific In Micementioning
confidence: 99%
“…Indeed, urinary THP reduction has been associated with certain pathological conditions, including acute tubular necrosis, diabetic nephropathy, hyperprostaglandin E syndrome, and active lupus nephritis (4,23,39,45,47). Although THP has been frequently used as an indicator for renal tubular function (46,57), the mechanisms by which THP gene expression are regulated have not been studied.…”
mentioning
confidence: 99%
“…[14] Our results corroborated with several others wherein decreased urinary Uromodulin levels have been reported in CKD patients. [6][7][8][9][10] Pracjczer et al [14] have reported that eGFR correlated positively with urinary Uromodulin levels but negatively with serum Uromodulin levels. However, they have further reported that in a subgroup of patients with lowest eGFR, urinary as well as serum Uromodulin levels were lowest.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Decreased urinary excretion of Uromodulin in parallel with the decrease in glomerular filtration rate (GFR) has been documented. [6][7][8][9][10] Although it is targeted to the apical membrane of TAL cells and secreted into the lumen, detectable levels are also found in venous blood. [11] In order to investigate the potential involvement of Uromodulin in CKD, paired samples of urine and serum were analysed for Uromodulin levels from CKD patients at different stages and correlated with estimated Glomerular Filtration Rate (eGFR) and with renal profile to determine its role in CKD.…”
Section: Introductionmentioning
confidence: 99%